KINEMATIC ANALYSIS OF HIP JOINT MODIFICATIONS IN SWITCH LEAP: COMPENSATORY MECHANISMS DUE TO REDUCED MOBILITY IN THIS AREA - Cerasela DOMOKOS; Anca DRAGOMIR; Martin Petru DOMOKOS; Cristian NEGREA; Eugen BOTA; Silvia-Nicoleta MIRICA; Adrian NAGEL; Martin Petru DOMOKOS (Cluj University Press, 2022)
Artistic gymnastics include a series of artistic elements where the joints' mobility represents an essential factor for the accuracy of the execution in both beam and floor routines. The reduced mobility is responsible for the occurrence of compensatory movements. This type of repetitive and long-term compensations can damage the joints involved in execution of an accurate switch leap element. The aim of the study was to analyze the compensatory mechanisms due to reduced mobility in the hip joint that can occur during the execution of a switch leap. 6 female gymnasts (8-10 years) from C.S.S.1 Timisoara have been analyzed when they executed switch leap on the floor. The kinematic analysis was carried using inertial sensors for movement tracking technology. The evaluated parameters were: leg separation angle (LSA), lateral pelvic tilt (LPT) and pelvic rotation (PR). The data revealed a LSA of 137.5± 2.239° which corresponds to the second level of penalty (0.30 points). The compensatory movements were revealed by the level of LPT and pelvic rotation. Depending on the front leg, the compensatory tilt, represented by the elevation of the hip joint, was found on the right or left part accordingly. Regarding the pelvic rotation, this is performed in the backward direction on the same part with the tilt. The kinematic analysis of the switch leap element provides supplementary data that can be taken into consideration by the gymnasts and coaches during the training period in order to reduce the risk of injuries and the risk of falling from the beam.